The Sweden Count 2000 - Skog, Margareta (Lund University, 2015)
The data file belonging to this study contains information about participation in services and worships at approximately 5,900 congregations, corps and religious groups across Sweden during the weekend of 24 - 26 September 1999. The survey was sent to roughly 6,500 congregations, corps and groups and a response rate of around 90% was thus reached. Well over half a million participations were registered during the weekend, in communities spanning over Christianity, Judaism, Islam, Bahá'í, Hinduism, Sikhism, Buddhism and "new movements" including New Age movements, Neopaganism, Neo-Hindu movements, the Church of Scientology etc. Four pieces of information were gathered: 1) day and time of the religious activity, 3) type of religious activity, 3) number of participants, 4) whether the activity was ecumenical or not.

Purpose:

What did religious Sweden look like just before the turn of the millennium 2000? Answering this question was the purpose of the Sweden Count 2000. More specifically, the study examines the number of visits to congregations and religious societies during a weekend of September 1999.

The dataset contains a data file with information on the number of visits to congregations and religious societies in Sweden during the weekend of 24th - 26th September 1999.

Datafilen i den här studien innehåller information om deltagande i gudstjänster och andakter hos ungefär 5900 församlingar, kårer och religiösa grupper i hela Sverige helgen 24-26 september 1999. Enkäten skickades ut till runt 6500 församlingar, kårer och grupper och fick alltså en svarsfrekvens på cirka 90%. Drygt en halv miljon besök registrerades under helgen hos samfund inom kristendom, judendom, islam, bahá'í, hinduism, sikhism, buddhism och "nya rörelser" som innefattar bland annat new age-rörelser, nyhedendom, nyhinduiska rörelser, scientologikyrkan m.fl. Fyra bitar information samlades in: 1) dag och tidpunkt för den religiösa aktiviteten, 2) typ av religiös aktivitet, 3) antal deltagare, 4) huruvida aktiviteten var ekumenisk eller inte.

Syfte:

Hur såg det religiösa Sverige ut inför millennieskiftet år 2000? Att besvara denna fråga var syftet med Sverigeräkningen 2000. Mer specifikt undersöker studien antalet besök hos församlingar och föreningar med religiösa ändamål under en helg i september 1999.

Datasetet består av en datafil med information om antal besök hos 6500 församlingar och religiösa föreningar i Sverige under helgen 24-26 september 1999.
Sverigeräkningen 2000
Keywords: religious attendance; religiöst deltagande; listening to music; musiklyssnande; islam; islam; church; kyrka; baptisms; dop; weddings; bröllop; religious affiliation; religiös tillhörighet; religious practice; religionsutövning; religious communities; religiösa församlingar; religious groups; religiösa grupper; judaism; judendom; folk cultures; folkkulturer; meditation; meditation; mysticism; mysticism; religious behaviour; religiöst beteende; religious ceremonies; religiösa ceremonier; attendance; närvaro; appointments; träffar; religious societies; religiösa samfund; religious institutions; religiösa institutioner; religious movements; religiös rörelse; funerals; begravningar; buddhism; buddhism; minority groups; minoritetsgrupp; hinduism; hinduism; catholicism; katolicism; christianity; kristendom; orthodoxy; ortodoxi; protestantism; protestantism; sikhism; sikhism; survey data; surveydata; Minorities; Minoriteter; Religion and values; Religion och värderingar; Religious Studies; Religionsvetenskap